2013
DOI: 10.1890/12-0681.1
|View full text |Cite
|
Sign up to set email alerts
|

Development of microbial‐enzyme‐mediated decomposition model parameters through steady‐state and dynamic analyses

Abstract: We developed a microbial-enzyme-mediated decomposition (MEND) model, based on the Michaelis-Menten kinetics, that describes the dynamics of physically defined pools of soil organic matter (SOC). These include particulate, mineral-associated, dissolved organic matter (POC, MOC, and DOC, respectively), microbial biomass, and associated exoenzymes. The ranges and/or distributions of parameters were determined by both analytical steady-state and dynamic analyses with SOC data from the literature. We used an improv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
304
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 224 publications
(319 citation statements)
references
References 66 publications
15
304
0
Order By: Relevance
“…They further concluded that the MM kinetics is applicable when the substrate concentration far exceeds the enzyme concentration, and the RMM kinetics is applicable when either the enzyme concentration far exceeds the substrate concentration or vice versa. The condition for the MM kinetics to be applicable as provided by Wang and Post (2013) was however much narrower than that was proposed in some earlier studies. For instance, Borghans et al (1996) showed that the MM kinetics is a good approximation to the quadratic kinetics when enzyme concentration is far smaller than the sum of the substrate concentration and the Michaelis-Menten constant (Palsson, 1987;Segel, 1988;Segel and Slemrod, 1989).…”
Section: Introductionmentioning
confidence: 74%
See 3 more Smart Citations
“…They further concluded that the MM kinetics is applicable when the substrate concentration far exceeds the enzyme concentration, and the RMM kinetics is applicable when either the enzyme concentration far exceeds the substrate concentration or vice versa. The condition for the MM kinetics to be applicable as provided by Wang and Post (2013) was however much narrower than that was proposed in some earlier studies. For instance, Borghans et al (1996) showed that the MM kinetics is a good approximation to the quadratic kinetics when enzyme concentration is far smaller than the sum of the substrate concentration and the Michaelis-Menten constant (Palsson, 1987;Segel, 1988;Segel and Slemrod, 1989).…”
Section: Introductionmentioning
confidence: 74%
“…[S] T proposed in Wang and Post (2013). I also note that the derivation of the RMM kinetics does not take into account the mass balance constraint for enzymes (Eq.…”
Section: The Reverse Michaelis-menten Kineticsmentioning
confidence: 99%
See 2 more Smart Citations
“…Microbially-explicit models (e.g., MIMICS, MEND) are rapidly becoming more sophisticated and are readily amenable to modules that represent ecological assembly processes [70,71]. As models begin to consider microbial ecology, there is a need to decipher linkages among spatiotemporal microbial processes and ecosystem-level biogeochemical function.…”
Section: Implications For Ecosystem Modelsmentioning
confidence: 99%